Pressureless sintering, additive-free, high-density and low-oxygen-content diboride ceramic and preparation method thereof

By embedding the reducing powder at a reducing atmosphere generated by the high temperature, the problem of difficult to prepare diboride ceramics with high density and low oxygen content under pressure-free sintering technology is solved, and high density ceramic preparation without additives is achieved.

CN119504265APending Publication Date: 2025-02-25WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411450410.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to prepare diboride ceramics with high density and low oxygen content without adding sintering aids through pressure-free sintering technology.

Method used

The reducing atmosphere generated by embedded reducing powders (such as B4C, C or B powder) at high temperature is used to remove oxygen impurities in the ceramic body, thereby achieving densification of diboride ceramics and achieving low oxygen content.

Benefits of technology

Diboride ceramics with high density (greater than 95%) and low oxygen content can be achieved without adding sintering aid, avoiding the problem of sintering aid residue and ensuring the purity of the ceramic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504265A_ABST
    Figure CN119504265A_ABST
Patent Text Reader

Abstract

The invention discloses pressureless sintering, additive-free, high-density and low-oxygen-content diboride ceramic and a preparation method thereof, and belongs to the field of non-oxide structural ceramic. The preparation method comprises the following steps: by taking diboride (MeB2) powder as a raw material, carrying out compression molding, embedding in reducing powder, and carrying out two-step pressureless sintering, so as to obtain the diboride ceramic. According to the method, oxygen impurities in the ceramic body can be effectively removed through the reducing atmosphere generated by embedding the reducing powder at a high temperature, the low-oxygen-content diboride ceramic can be prepared without excessively depending on the purity of the raw materials, meanwhile, the problem that the sintering aid is left on the ceramic matrix due to the addition of the sintering aid is avoided, and the method is suitable for large-scale production. And the purity of the ceramic is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of non-oxide structural ceramics, and in particular to a pressureless sintered, additive-free, highly dense, low-oxygen-content diboride ceramic and a preparation method thereof. Background Art

[0002] Transition metal diboride ceramics have a hexagonal structure similar to AlB2. Boron atoms are connected by strong covalent bonds, and metal atoms and boron atoms are connected by ionic bonds. Therefore, diboride ceramics have a high melting point, hardness, strength, excellent wear resistance, good structural stability and oxidation resistance, and can be used in many fields such as bulletproof armor, aerospace, and cutting tools.

[0003] However, due to the ultra-high melting point and strong covalent bond characteristics of diboride, the corresponding powder has poor sintering activity and low self-diffusion coefficient, which makes it difficult to densify its powder by conventional sintering methods. In order to obtain dense diboride ceramics, higher sintering temperature and sintering pressure are often required; however, pressure sintering technology limits the preparation of large-sized and complex-shaped ceramics, and the cost of pressure sintering is high, which is not conducive to its large-scale promotion in industry.

[0004] Pressureless sintering is a method that can achieve near-net-shape preparation of parts and has great potential for large-scale industrial application. Therefore, pressureless sintering is applied to the sintering preparation of diboride ceramics.

[0005] Compared with pressure sintering technology, since pressureless sintering lacks auxiliary pressure, in order to obtain dense pressureless sintered samples, it is usually necessary to add a certain amount of sintering aids to the powder, such as carbon (C), B4C, boron (B) that can remove "oxygen contamination" on the surface of the powder and promote ceramic densification, as well as low-melting-point metals Ni and Co that can produce liquid phase during the sintering process. For example, Zhu et al. used phenolic resin as C sintering aid and prepared ZrB2 ceramics with density > 99% by pressureless sintering at 1900℃ (J.Eur.Ceram.Soc., 2007, 459:167-171.); similar results can be obtained by using B4C as sintering aid or by combining B4C and C as sintering aids (J.Am.Ceram.Soc., 2007, 90(11):3660-3663.); Yang et al. used Ni as sintering aid and achieved (Hf 0.2 V 0.2 Ta 0.2 Ti 0.2 Nb 0.2 )B2、(Zr 0.2 V 0.2 Ta 0.2 Ti 0.2 Nb 0.2)B2 and (Cr 0.2 V 0.2 Ta 0.2 Ti 0.2 Nb 0.2 ) Densification of B2 (J.Alloys Compd.,2023,952:169975.).

[0006] In the technology of preparing diboride ceramics by pressureless sintering, although the addition of sintering aids can promote the densification of diboride ceramics, the second phase remaining in the diboride matrix usually reduces its room temperature or high temperature mechanical properties. At present, there is no good way to prepare high-density diboride ceramics without sintering aids using pressureless sintering technology. Summary of the invention

[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a pressureless sintering, additive-free, highly dense and low-oxygen diboride ceramic and a preparation method thereof. The present invention does not need to add any sintering aid to the diboride powder, and can achieve its densification through pressureless sintering technology, and the prepared diboride ceramic has a high density. The ceramic body is embedded and sintered with reducing powders. Under high temperature conditions, these reducing powders produce a reducing atmosphere, which penetrates into the ceramic body through the connected pores in the body and reacts with the "oxygen pollution" covering the surface of the powder, thereby significantly promoting the densification of the diboride ceramic. The present invention can effectively remove oxygen impurities in the ceramic body by embedding the reducing atmosphere generated by the reducing powder at high temperature, and can prepare diboride ceramics with low oxygen content without relying too much on the purity of the raw materials. At the same time, it avoids the problem of sintering aids remaining in the ceramic matrix due to the addition of sintering aids, thereby ensuring the purity of the ceramic.

[0008] To achieve the above object, the present invention is implemented by the following technical solutions:

[0009] The invention provides a method for preparing pressureless sintering, additive-free, high-density and low-oxygen-content diboride ceramics.

[0010] The method for preparing the pressureless sintering additive-free, highly dense and low-oxygen diboride ceramics comprises the following steps: using diboride MeB2 powder as raw material, pressing and molding it, embedding it in reducing powder, and performing two-step pressureless sintering to obtain the diboride ceramics.

[0011] As a further optimization scheme of the present invention, the particle size of the diboride MeB2 powder is 0.1 μm to 5 μm, and the oxygen content is 0.05 wt% to 5 wt%.

[0012] As a further optimization scheme of the present invention, the metal element Me in the diboride MeB2 powder is composed of one or more elements, and the elements are selected from titanium (Ti), zirconium (Zr), hafnium (Hf), niobium Nb, tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W) and vanadium (V).

[0013] As a further optimization scheme of the present invention, the pressure of the pressing molding is 30 to 500 MPa, and the holding time is 0.5 to 10 min.

[0014] As a further optimization scheme of the present invention, the reducing powder includes at least one of boron carbide (B4C), graphite (C), and boron (B) powder.

[0015] As a further optimization scheme of the present invention, the mass fractions of B4C, C and B powder in the mixed powder are x, y and z respectively, wherein x+y+z=1, 0≤x≤1, 0≤y≤1, 0≤z≤1.

[0016] As a further optimization scheme of the present invention, the two-step pressureless sintering is specifically to first heat the temperature to 1400-1700° C. under vacuum conditions and keep the temperature, and then heat the temperature to 1900-2300° C. under inert gas conditions and keep the temperature.

[0017] As a further optimization scheme of the present invention, the first heating rate of the two-step pressureless sintering is 10-40°C / min, and the insulation time is 0.5-1h; the first heating rate of the two-step pressureless sintering is 5-10°C / min, and the insulation time is 1-3h.

[0018] As a further optimization solution of the present invention, the inert gas is argon (Ar) or helium (He).

[0019] The present invention also provides a pressureless sintered, additive-free, highly dense and low-oxygen-content diboride ceramic, which is prepared by the preparation method of the pressureless sintered, additive-free, highly dense and low-oxygen-content diboride ceramic provided by the present invention.

[0020] As a further optimization scheme of the present invention, the density of the diboride ceramic is greater than 95%, and the oxygen content is 0.01wt% to 0.3wt%.

[0021] The technical solution provided by the present invention has the following beneficial effects:

[0022] (1) The present invention does not need to add any sintering aids to the diboride powder, and densification is achieved through pressureless sintering technology, and the prepared ceramics have a high density. The ceramic body is embedded and sintered with reducing powders B4C, C or boron powder and their mixed powders. Under high temperature conditions, these reducing powders produce a reducing atmosphere, which penetrates into the ceramic body through the connected pores in the body and reacts with the "oxygen pollution" covering the surface of the powder, thereby significantly promoting the densification of the diboride ceramic. Without adding any sintering aids, diboride ceramics with a density greater than 95% can be prepared by pressureless sintering in a sintering temperature range of 1900 to 2300°C.

[0023] (2) The present invention can effectively remove oxygen impurities in the ceramic body by creating a reducing atmosphere at high temperature through embedding the reducing powder, and can prepare diboride ceramics with a low oxygen content without relying too much on the purity of the raw materials. At the same time, it avoids the problem of sintering aids remaining in the ceramic matrix due to the addition of sintering aids, thereby ensuring the purity of the ceramic. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The microscopic morphology of the polished surface of the diboride ceramic obtained in Example 1 of the present invention;

[0025] Figure 2 This is a microscopic morphology of the polished surface of the diboride ceramic obtained in Comparative Example 1 of the present invention;

[0026] Figure 3 This is a microscopic morphology of the fracture of the diboride ceramic obtained in Example 3 of the present invention;

[0027] Figure 4 This is a microscopic morphology of the fracture of the diboride ceramic obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.

[0029] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0030] Example 1

[0031] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0032] Step 1: (Ti0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 powder was pressed under a pressure of 500MPa for 5 minutes and then molded to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body; then fill a layer of B4C powder with a thickness of about 5mm in the graphite crucible, and then (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body is placed on the B4C powder, and finally a layer of B4C powder with a thickness of about 5mm is laid on it to complete the (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 embedding of ceramic body;

[0033] Step 2: The embedded (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 The B2 ceramic body was placed in an atmosphere sintering furnace, first heated to 1650°C at a heating rate of 40°C / min under vacuum conditions and kept warm for 0.5h, then introduced with Ar gas, heated to 2200°C at a heating rate of 10°C / min and kept warm for 2h, and after the end of the heat preservation, the heating was stopped and then cooled to room temperature with the furnace to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics.

[0034] The (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 ) The density of B2 ceramics is 97.8%, the oxygen content is 0.2wt%, and the Vickers hardness is 20.1±0.3GPa.

[0035] Example 2

[0036] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0037] Step 1: (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 powder was pressed under a pressure of 500MPa for 5 minutes and then molded to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body; then fill a layer of B4C powder with a thickness of about 5mm in the graphite crucible, and then (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body is placed on the B4C powder, and finally a layer of B4C powder with a thickness of about 5mm is laid on it to complete the (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 embedding of ceramic body;

[0038] Step 2: The embedded (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 The B2 ceramic body was placed in an atmosphere sintering furnace, first heated to 1650°C at a heating rate of 40°C / min under vacuum conditions and kept warm for 0.5h, then introduced with Ar gas, heated to 1900°C at a heating rate of 10°C / min and kept warm for 2h, and after the end of the heat preservation, the heating was stopped and then cooled to room temperature with the furnace to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics.

[0039] The (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 ) The density of B2 ceramics is 96.1%, the oxygen content is 0.3wt%, and the Vickers hardness is 19.7±0.6GPa.

[0040] Example 3

[0041] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0042] Step 1: (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 powder was pressed under a pressure of 400MPa for 5min and then molded to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body; then fill a layer of B4C powder with a thickness of about 5mm in the graphite crucible, and then (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body is placed on the B4C powder, and finally a layer of B4C powder with a thickness of about 5mm is laid on it to complete the (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 embedding of ceramic body;

[0043] Step 2: The embedded (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 The B2 ceramic body was placed in an atmosphere sintering furnace, first heated to 1700°C at a heating rate of 40°C / min under vacuum conditions and kept warm for 0.5h, then introduced with Ar gas, heated to 2200°C at a heating rate of 10°C / min and kept warm for 2h, and after the end of the heat preservation, the heating was stopped and then cooled to room temperature with the furnace to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics.

[0044] The fracture morphology of (Ti0.2Zr0.2Hf0.2Nb0.2Ta0.2)B2 ceramics prepared by the above steps is as follows: Figure 3 As shown, there are fewer pores in the sample and no obvious oxide second phase is observed.

[0045] The (Ti 0.2 Zr 0.2 Hf0.2 Nb 0.2 Ta 0.2 ) The density of B2 ceramics is 98.1%, the oxygen content is 0.01wt%, and the Vickers hardness is 20.9±0.6GPa.

[0046] Example 4

[0047] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0048] Step 1: (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 powder was pressed under a pressure of 400MPa for 5min and then molded to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body; then fill a layer of B4C powder with a thickness of about 5mm in the graphite crucible, and then (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body is placed on the graphite powder, and finally a layer of graphite powder with a thickness of about 5mm is laid on it to complete the (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 embedding of ceramic body;

[0049] Step 2: The embedded (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 The B2 ceramic body was placed in an atmosphere sintering furnace, first heated to 1400°C at a heating rate of 40°C / min under vacuum conditions and kept warm for 0.5h, then introduced with Ar gas, heated to 2100°C at a heating rate of 10°C / min and kept warm for 2h, and after the end of the heat preservation, the heating was stopped, and then cooled to room temperature with the furnace to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics.

[0050] The (Ti0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 ) The fracture morphology of B2 ceramics is as follows Figure 4 As shown, there are fewer pores in the sample.

[0051] The (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics have a density of 98.9%, an oxygen content of 0.05wt%, and a Vickers hardness of 20.1±0.3GPa.

[0052] Example 5

[0053] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0054] Step 1: (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 powder was pressed under a pressure of 400MPa for 5min and then molded to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 ) B2 ceramic body; then in the graphite crucible filled with a layer of about 5mm thick by 40wt% B4C powder and 60wt% graphite powder composed of mixed powder, then (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body is placed on the mixed powder, and finally a layer of the mixed powder with a thickness of about 5mm is spread on it to complete the (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 embedding of ceramic body;

[0055] Step 2: The embedded (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2The B2 ceramic body was placed in an atmosphere sintering furnace, first heated to 1650°C at a heating rate of 40°C / min under vacuum conditions and kept warm for 0.5h, then introduced with Ar gas, heated to 2100°C at a heating rate of 10°C / min and kept warm for 2h, and after the end of the heat preservation, the heating was stopped and then cooled to room temperature with the furnace to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics.

[0056] The (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 ) The density of B2 ceramics is 99.1%, the oxygen content is 0.04wt%, and the Vickers hardness is 21.3±0.5GPa.

[0057] Example 6

[0058] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0059] Step 1: ZrB2 powder with an oxygen content of 0.1wt% and an average particle size of 1μm is pressed under a pressure of 500MPa for 5min to obtain a ZrB2 ceramic body; then a layer of B4C powder with a thickness of about 5mm is spread on a graphite crucible, and then the ZrB2 ceramic body is placed on the spread B4C powder, and finally another layer of B4C powder with a thickness of about 5mm is spread to complete the embedding of the ZrB2 ceramic body;

[0060] Step 2: Place the embedded ZrB2 ceramic body in an atmosphere sintering furnace, first heat it to 1650℃ at a heating rate of 40℃ / min under vacuum conditions and keep it warm for 0.5h, then introduce Ar gas, heat it to 2300℃ at a heating rate of 5℃ / min, and keep it warm for 3h. After the insulation is completed, stop heating, and then cool it to room temperature with the furnace to obtain ZrB2 ceramics.

[0061] The density of the ZrB2 ceramic prepared in this embodiment is 97.3%, the oxygen content is 0.02wt%, and the Vickers hardness is 16.7±0.6GPa.

[0062] Example 7

[0063] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0064] Step 1: (Ti0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 powder is pressed under a pressure of 500MPa for 5min to obtain a HfB2 ceramic body; then a layer of B4C powder with a thickness of about 5mm is spread on the graphite crucible, and then the HfB2 ceramic body is placed on the spread B4C powder, and finally another layer of B4C powder with a thickness of about 5mm is spread to complete the embedding of the HfB2 ceramic body;

[0065] Step 2: Place the embedded HfB2 ceramic body in an atmosphere sintering furnace, first heat it to 1600°C at a heating rate of 40°C / min under vacuum conditions and keep it warm for 1 hour, then introduce Ar gas, heat it to 2300°C at a heating rate of 10°C / min, and keep it warm for 1 hour. After the insulation is completed, stop heating, and then cool it to room temperature with the furnace to obtain HfB2 ceramics.

[0066] The density of the HfB2 ceramic prepared in this embodiment is 95.5%, the oxygen content is 0.06wt%, and the Vickers hardness is 17.3±0.9GPa.

[0067] Example 8

[0068] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0069] Step 1: (Hf 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 powder was pressed under a pressure of 300MPa for 5min to obtain HfB2 ceramic body; then a layer of graphite powder with a thickness of about 5mm was spread in the graphite crucible, and then (Hf 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 ceramic body is placed on the graphite powder, and finally a layer of graphite powder with a thickness of about 5mm is laid on it to complete the (Hf 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 embedding of ceramic body;

[0070] Step 2: The embedded (Hf 1 / 3 Zr 1 / 3 Ta 1 / 3The B2 ceramic body was placed in an atmosphere sintering furnace, first heated to 1600°C at a heating rate of 40°C / min under vacuum conditions and kept at that temperature for 1 hour, then introduced with Ar gas, heated to 2000°C at a heating rate of 10°C / min and kept at that temperature for 1 hour, and after the end of the heat preservation, the heating was stopped, and then cooled to room temperature with the furnace to obtain (Hf 1 / 3 Zr 1 / 3Ta 1 / 3 )B2 ceramics.

[0071] The (Hf 1 / 3 Zr 1 / 3 Ta 1 / 3 ) The density of B2 ceramic is 95.1%, the oxygen content is 0.08wt%, and the Vickers hardness is 18.6±0.3GPa.

[0072] Example 9

[0073] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0074] Step 1: HfB2 powder with an oxygen content of 0.5wt% and an average particle size of 5μm is pressed under a pressure of 500MPa for 10min to obtain a HfB2 ceramic body; then a layer of boron powder with a thickness of about 5mm is spread on a graphite crucible, and then the HfB2 ceramic body is placed on the spread boron powder, and finally another layer of boron powder with a thickness of about 5mm is spread to complete the embedding of the HfB2 ceramic body;

[0075] Step 2: Place the embedded HfB2 ceramic body in an atmosphere sintering furnace, first heat it to 1600°C at a heating rate of 40°C / min under vacuum conditions and keep it warm for 1 hour, then introduce Ar gas, heat it to 2300°C at a heating rate of 10°C / min, and keep it warm for 3 hours. After the insulation is completed, stop heating, and then cool it to room temperature with the furnace to obtain HfB2 ceramics.

[0076] The density of the HfB2 ceramic prepared in this embodiment is 96.6%, the oxygen content is 0.06wt%, and the Vickers hardness is 18.9±0.6GPa.

[0077] Example 10

[0078] A method for preparing a pressureless sintering, additive-free, high-density, and low-oxygen diboride ceramic, the specific steps of which are as follows:

[0079] Step 1: HfB2 powder with an oxygen content of 0.5wt% and an average particle size of 5μm is pressed and molded at a pressure of 500MPa for 0.5min to obtain an HfB2 ceramic body; then a layer of boron powder with a thickness of about 5mm is spread in a graphite crucible, and then the HfB2 ceramic body is placed on the spread boron powder, and finally another layer of boron powder with a thickness of about 5mm is spread to complete the embedding of the HfB2 ceramic body;

[0080] Step 2: Place the embedded HfB2 ceramic body in an atmosphere sintering furnace, first heat it to 1600°C at a heating rate of 40°C / min under vacuum conditions and keep it warm for 1 hour, then introduce Ar gas, heat it to 2300°C at a heating rate of 10°C / min, and keep it warm for 3 hours. After the insulation is completed, stop heating, and then cool it to room temperature with the furnace to obtain HfB2 ceramics.

[0081] The density of the HfB2 ceramic prepared in this embodiment is 95.3%, the oxygen content is 0.04wt%, and the Vickers hardness is 18.1±0.3GPa.

[0082] Comparative Example 1

[0083] A method for preparing diboride ceramics, the specific steps are as follows:

[0084] Step 1: (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 powder was pressed into shape at a pressure of 500MPa for 5min, and then (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramic body is placed in a graphite crucible.

[0085] Step 2: (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 The B2 ceramic body was placed in an atmosphere sintering furnace, first heated to 1650°C at a heating rate of 40°C / min under vacuum conditions and kept at this temperature for 0.5h, then introduced with Ar gas, heated to 2200°C at a heating rate of 10°C / min, and kept at this temperature for 2h. After the insulation was completed, the heating was stopped, and then the body was cooled to room temperature with the furnace to obtain (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics.

[0086] The (Ti 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2 ceramics have a density of 83%, an oxygen content of 1.6wt%, and a Vickers hardness of 9.1±1.1GPa.

[0087] It can be seen from Example 1 and Comparative Example 1 that, under the same sintering process, there are significant differences between the ceramic samples embedded with B4C powder and sintered without embedding. Compared with Comparative Example 1, the sample embedded with B4C powder in Example 1 has a significantly higher density, so its Vickers hardness is higher; at the same time, the oxygen content of the ceramic prepared in Example 1 is lower, and its oxygen content is significantly reduced compared with the original powder, while the oxygen content of the sample prepared in Comparative Example 1 is only slightly reduced compared with the original powder. Figure 1 This is a microscopic morphology of the ceramic polishing surface obtained in Example 1. Figure 2 The microscopic morphology of the ceramic polishing surface obtained in Comparative Example 1 is shown in FIG. Figure 1 It can be seen that the ceramic prepared in Example 1 has fewer pores and no obvious second phase is found, while the ceramic prepared in Comparative Example 1 has more connected pores, proving that the sintering of the sample has not been completed in the middle stage.

[0088] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a pressureless sintered, additive-free, high-density, low-oxygen diboride ceramic, characterized in that: The following steps are involved: The diboride MeB2 powder is used as a raw material, which is pressed and molded, then embedded in a reducing powder and subjected to two-step pressureless sintering to obtain the diboride ceramic.

2. The method for preparing the pressureless sintering additive-free, high-density and low-oxygen diboride ceramic according to claim 1, characterized in that: The particle size of the diboride MeB2 powder is 0.1 μm to 5 μm, and the oxygen content is 0.05 wt% to 5 wt%.

3. The method for preparing the pressureless sintering additive-free, high-density and low-oxygen diboride ceramic according to claim 1, characterized in that: The metal element Me in the diboride MeB2 powder is composed of one or more elements, and the elements are selected from titanium, zirconium, hafnium, niobium, tantalum, chromium, molybdenum, tungsten and vanadium.

4. The method for preparing the pressureless sintering additive-free, high-density and low-oxygen diboride ceramic according to claim 1, characterized in that: The compression molding pressure is 30-500 MPa, and the pressure holding time is 0.5-10 min.

5. The method for preparing pressureless sintering additive-free, high-density and low-oxygen diboride ceramics according to claim 1, characterized in that: The reducing powder includes at least one of B4C, C and B powder.

6. The method for preparing pressureless sintering additive-free, high-density and low-oxygen diboride ceramics according to claim 5, characterized in that: The mass fractions of B4C, C and B powder in the mixed powder are x, y and z respectively, wherein x+y+z=1, 0≤x≤1, 0≤y≤1, 0≤z≤1.

7. The method for preparing pressureless sintering additive-free, high-density and low-oxygen diboride ceramics according to claim 1, characterized in that: The two-step pressureless sintering specifically comprises firstly heating the temperature to 1400-1700° C. under vacuum conditions and then heating the temperature to 1900-2300° C. under inert gas conditions and then heating the temperature.

8. The method for preparing pressureless sintering additive-free, high-density and low-oxygen diboride ceramics according to claim 7, characterized in that: The first heating rate of the two-step pressureless sintering is 10-40°C / min, and the insulation time is 0.5-1h; the first heating rate of the two-step pressureless sintering is 5-10°C / min, and the insulation time is 1-3h; the inert gas is argon or helium.

9. A pressureless sintered, additive-free, high-density, low-oxygen diboride ceramic, characterized in that: The diboride ceramic is prepared by the method for preparing the pressureless sintering, additive-free, highly dense and low-oxygen diboride ceramic according to any one of claims 1 to 8.

10. The pressureless sintered additive-free, high-density, low-oxygen diboride ceramic according to claim 9, characterized in that: The density of the diboride ceramic is greater than 95%, and the oxygen content is 0.01wt% to 0.3wt%.